Chlorpyrifos exposure induces inflammatory and immune dysregulation: An integrative in silico and in vitro analysis - Chen-Yu Chiang; Shih-Pin Chen; Ci-Wen Luo; Chun-Hung Su; Shiuan-Shinn Lee; Wen-Ying Chen; Chun-Jung Chen; Ching-Chi Tseng; Pin-Tzu Chen; Yin-Che Lu; Yu-Hsiang Kuan (Pesticide Biochemistry and Physiology, 2026)

Dual carbon source driven metabolic coupling shapes microalgal-bacterial granular sludge stability - Chenkai Liu; Chi Che; Peiting Huang; Jiachun Gao; Siyu Wang; Bin Ji (Environmental Research, 2026)

Depth heterogeneity within surface soils substantially affects microbial abundance, diversity, and co-occurrence patterns - Guanyu Chai; Yuan Du; Zelin Wang; Kaifang Liu; Yuan Chi; Yi Duan; Shuo Ma; Xin Hu; Rongxiao Che; Jianxing Li; Wenjun Liu; Dong Liu (Journal of Soils and Sediments, 2026)

Full-scale field tests on energy storage cabinets under thermal runaway and firefighting response - Chih-Chiang Hsieh; Ming-Che Sung; Chi-Min Shu; Chia-Chin Chang (Process Safety and Environmental Protection, 2026)

Caffeinated chewing gum improves military performances in special forces soldiers - Yi-Jie Shiu; Che-Hsiu Chen; Hung-Yu Lin; Chia-Cheng Yang; Chi-Wen Yen; Han-Yuan Chang; Hsuan-Ta Chen; Chih-Hui Chiu (European Journal of Applied Physiology, 2026)

Doxorubicin-Induced Cardiotoxicity in Breast Cancer: Mechanistic Pathways, Pharmacogenomic Modifiers, and Translational Strategies - Chi-Tong Kuok; Hao-Wei Lee; Chen-Yu Huang; Yu-Che Cheng; Shih-Chang Lin; Jiun-Wen Guo (Cardiovascular Toxicology, 2026)

Luteolin-stabilized pickering emulsion for encapsulating Enterococcus hirae: preparation, characterization, and synergistic effects on hyperuricemia - Chengtao Han; Songhao Che; Hui-Min Li; Yan-Yu Chi; Jun-Yan Xiang; Qiuhong Xie; Hongyu Xiang (Food Research International, 2026)

Corrigendum to “AI-driven process-tolerant BioFET sensing model for precise biliary atresia diagnosis of infants with a single drop of blood” [Chem. Eng. J. (2026), volume 531, 1 March 2026, 173939] - Chia-Kai Lin; Chi-Ming Ku; Chia-Che Wu; Yi-Fang Wu; Huey-Ling Chen; Yueh-Ju Hou; Arnab Pal; Zong-Hong Lin; Chee-Seng Lee; Tzong-Rong Ger; Yu-Lin Wang (Chemical Engineering Journal, 2026)

AI-driven process-tolerant BioFET sensing model for precise biliary atresia diagnosis of infants with a single drop of blood - Chia-Kai Lin; Chi-Ming Ku; Chia-Che Wu; Yi-Fang Wu; Heuy-Ling Chen; Yueh-Ju Hou; Arnab Pal; Zong-Hong Lin; Chee-Seng Lee; Tzong-Rong Ger; Yu-Lin Wang (Chemical Engineering Journal, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Boosting catalytic activity toward industrial water electrolysis: Ag–triggered dual–site activation in NiFe LDH for ultra–efficient oxygen evolution reaction - Habib Gemechu Edao; Chia-Yu Chang; Woldesenbet Bafe Dilebo; Chemeda Barasa Guta; Keseven Lakshmanan; Endalkachew Asefa Moges; Fikiru Temesgen Angerasa; Baru Debtera Bejena; Chun-Chi Chang; Wei-Sheng Liao; Meng-Che Tsai; Wei-Nien Su; et al. (Chemical Engineering Journal, 2026)

Exosome Purification Strategy Influences the Regenerative Efficacy of Dental Pulp Stem Cell-Derived Exosomes in Bone Regeneration - Borae Lee; Chia-Yi Hung; Yu-Ting Chien; Chi-Che Hsieh; Wei-Hao Cheng; Ya-Hui Chan; Pin-Chuang Lai; Sheng-Wei Feng (Stem Cell Reviews and Reports, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

Chemical structure and bioactivities of a sulfated polysaccharide from precious medicinal fungi - Mei-Kuang Lu; Chi-Hsein Chao; Tsu-Yuan Chang; Ming-Che Cheng; Yu-Chi Hsu; Chia-Chuan Chang (Phytochemistry Letters, 2025)

Functional oligosaccharides derived from the degradation of natural Dendrobium polysaccharides by human gut microbes regulate physiological factors associated with type-2 diabetes - Ming-Che Cheng; Hsi-Mei Chen; Bao-Jiun Bai; Tsu-Yuan Chang; Meng-Chin Chen; Yen- Ting Lin; Chi-Kung Ni; Mei-Kuang Lu; Hui-Kang Liu; Chia-Chuan Chang (Phytochemistry Letters, 2025)

Graft-modified amphiphilic dendron/polyimide regular through-pore composite membranes for oil/water separation - Chien-Chieh Hu; Cai-Syuan Sung; Ru-Jong Jeng; Chien-Hsin Wu; Ying-Chi Huang; Huai-Che Chang; Kueir-Rarn Lee; Juin-Yih Lai (Chemical Engineering Journal, 2025)

Growth and reproductive performance of reciprocal crossbred sex-linked dwarf and non-dwarf Taiwan Country chickens - Samkelo Mlandvo Motsa; Tsung-Che Tu; Szu-Hung Chen; Pin-Chi Tang; Chih-Feng Chen (Tropical Animal Health and Production, 2025)

Biopolymer-amended geosynthetic clay liners for landfills and contaminated sites: Gas and hydraulic performance - Ying-Zhen Li; Heng Zhuang; Ji-Ying Fan; Wei-Yi Xia; Jia-Lei Wan; Chi Che; Yan-Jun Du (Environmental Research, 2025)

Estimating the Permeability–Depth Relation of Slate Formation for Geothermal Project - Xuan-Xinh Nguyen; Che-Wei Yeh; Tan-Minh Le; Jia-Jyun Dong; Chih-Hsi Liu; Chi-Ping Pan (Rock Mechanics and Rock Engineering, 2025)

SEBS-amended in-situ mixed wall material for diesel-contaminated groundwater management - Zhe-Yuan Jiang; Xian-Lei Fu; Fei Jin; Chi Che; Zhong-Yuan Li; Guojun Cai; Yan-Jun Du (Journal of Hazardous Materials, 2025)

Numerical simulation of GPR via Leapfrog ADI-FDTD - Bohua Wang; Hongyan Shen; Han Che; Shuai Liu; Chi Wang; Chengwei Zhang; Hao Wang; Shisheng Feng; Kanglong Wang (Journal of Applied Geophysics, 2025)

Lipid profiles of green conversion from corn-ethanol co-product via Aspergillus niger - Weiwei Fan; Ayong Wang; Xiaoying Che; Siyu Xu; Ming Chen; Zhanyou Chi (Bioresource Technology, 2025)

Inversion of Rayleigh wave dispersion curves integrating the Osprey–Cauchy and Pigeon-inspired optimization algorithm - Shuai Liu; Hongyan Shen; Han Che; Bohua Wang; Chi Wang; Chengwei Zhang; Guangzhou Shao; Shisheng Feng; Hao Wang; Kanglong Wang (Acta Geophysica, 2025)

Plasmonic Au-NPs photodecorated on NiCoLDH nanosheets as a flexible SERS sensor for the real-time detection of fipronil - Nazar Riswana Barveen; Sathishkumar Chinnapaiyan; Che-Wei Zeng; Chi-Hsien Huang; Yen-Yu Lin; Yu-Wei Cheng (Journal of Hazardous Materials, 2024)

In enzymatic reactions, the reverse reaction reduces product noise - Ching-Chu Hsieh; Yung-Chun Lin; Wei-Bo Lin; Che-Chi Shu (BioSystems, 2024)

Mesenchymal Stem Cells Overexpressing FGF21 Preserve Blood-Brain Barrier Integrity in Experimental Ischemic Stroke - Phuong Thao Do; De-Maw Chuang; Chung-Che Wu; Chi-Zong Huang; Yen-Hua Chen; Shuo-Jhen Kang; Yung-Hsiao Chiang; Chaur-Jong Hu; Kai-Yun Chen (Translational Stroke Research, 2024)

Organic carbon decomposition temperature sensitivity positively correlates with the relative abundance of copiotrophic microbial taxa in cropland soils - Yuan Du; Anlan Yu; Yuan Chi; Zelin Wang; Xinrui Han; Kaifang Liu; Qiuping Fan; Xin Hu; Rongxiao Che; Dong Liu (Applied Soil Ecology, 2024)

The role of ALDH1A1 in glioblastoma proliferation and invasion - Yu-Kai Huang; Tzu-Ming Wang; Chi-Yu Chen; Chia-Yang Li; Shu-Chi Wang; Khushboo Irshad; Yuan Pan; Kun-Che Chang (Chemico-Biological Interactions, 2024)

Dual-Targeting EGCG/NO-Supplying protein assembled nanoparticles with Multi-Synergistic effects against atherosclerosis - Chi Lin; Tsai-Mu Cheng; Yun-Chun Liu; Fang-Yu Hsu; Chun-Ming Shih; Min-Lang Tsai; Chun-Che Shih; Fwu-Long Mi (Chemical Engineering Journal, 2024)

Phylogeny and genetic diversity of Echinometra sea urchin in Taiwan - Mei-Fang Lin; Ming-Che Yang; Yi-Yuan Lin; Sheng-Chi Chung; Li-Lian Liu (Marine Biology Research, 2024)

Protective effects of baffles with different positions, row spacings, heights on debris flow impact - Xinpo Sun; Min Chen; Yuzhang Bi; Lu Zheng; Chi Che; Ao Xu; Zijian Tian; Zheyuan Jiang (Journal of Mountain Science, 2024)

Evaluating the Flocculation and Dye Recovery Potential of Cationic Dye Basic Blue 41 Using a Natural Flocculant Derived from Colletotrichum gloeosporioides - Chun-Yung Wu; Che-Chi Shu (Water, Air, & Soil Pollution, 2024)

Characteristics and impacts of fine particulates from the largest power plant plume in Taiwan - Ming-Tung Chuang; Charles C.-K Chou; Chung-Te Lee; Ja-Huai Lee; Wei-Che Lin; Chuan-Yao Lin; Wei-Nai Chen; Yi-Ying Chen; Kai-Hsien Chi (Atmospheric Pollution Research, 2024)

Effects of occupational exposure to metal fume PM2.5 on lung function and biomarkers among shipyard workers: a 3-year prospective cohort study - Huan Minh Tran; Ching-Huang Lai; Wei-Liang Chen; Chung Ching Wang; Che-Wei Liang; Chi-Yu Chien; Chih-Hong Pan; Kai-Jen Chuang; Hsiao-Chi Chuang (International Archives of Occupational and Environmental Health, 2024)
Objective This study investigates the associations of α1-antitrypsin, inter-α-trypsin inhibitor heavy chain (ITIH4), and 8-isoprostane with lung function in shipyard workers exposed to occupational metal fume fine particulate matter (PM 2.5 ), which is known to be associated with adverse respiratory outcomes. Methods A 3-year follow-up study was conducted on 180 shipyard workers with 262 measurements. Personal exposure to welding fume PM 2.5 was collected for an 8-h working day. Pre-exposure, post-exposure, and delta (∆) levels of α1-antitrypsin, ITIH4, and 8-isoprostane were determined in urine using enzyme-linked immunosorbent assays. Post-exposure urinary metals were sampled at the beginning of the next working day and analyzed by inductively coupled plasma-mass spectrometry. Lung function measurements were also conducted the next working day for post-exposure. Results An IQR increase in PM 2.5 was associated with decreases of 2.157% in FEV 1 , 2.806% in PEF, 4.328% in FEF 25% , 5.047% in FEF 50% , and 7.205% in FEF 75% . An IQR increase in PM 2.5 led to increases of 42.155 µg/g in ∆α1-antitrypsin and 16.273 µg/g in ∆ITIH4. Notably, IQR increases in various urinary metals were associated with increases in specific biomarkers, such as post-urinary α1-antitrypsin and ITIH4. Moreover, increases in ∆ α1-antitrypsin and ∆ITIH4 were associated with decreases in FEV 1 /FVC by 0.008% and 0.020%, respectively, and an increase in ∆8-isoprostane resulted in a 1.538% decline in FVC. Conclusion Our study suggests that urinary α1-antitrypsin and ITIH4 could indicate early lung function decline in shipyard workers exposed to metal fume PM 2.5 , underscoring the need for better safety and health monitoring to reduce respiratory risks. Graphical abstract

Structure-specific metabolism of flavonol molecules by Bacillus subtilis var. natto BCRC 80517 - Che-Wei Wang; Hsin-Ya Tsai; Chen Hsu; Ching-Chun Hsieh; I-Shu Wang; Chi-Fon Chang; Nan-Wei Su (Food Chemistry, 2024)

Research on methods and strategies of green design carbon reduction for bicycle industry in Taiwan from perspective of product life cycle - Jui-Che Tu; Shi-Chen Luo; Pei-Chi Huang; Xiu-Yue Zhang (Environment, Development and Sustainability, 2023)

Duplicated paralog of sulfide: quinone oxidoreductase contributes to the adaptation to hydrogen sulfide-rich environment in the hydrothermal vent crab, Xenograpsus testudinatus - Chi Chen; Guan-Chung Wu; Yao-Tse Chung; Hau-Wen Li; Pei-Hsuan Chou; Yung-Che Tseng; Chieh-Jhen Chen; Sylvie Dufour; Ching-Fong Chang (Science of The Total Environment, 2023)

New ent -kaurene and germacrene derivatives from Mesona procumbens Hemseley and their biological activity - Jerome G. Ganzon; Chia-Ching Liaw; Yu-Chi Lin; Zhi-Hu Lin; Chang-Hung Wang; Che-Yi Chen; Kuo-Hsiang Chuang; Yao-Haur Kuo (Natural Product Research, 2023)

The city-wide full-scale interactive application of sewage surveillance programme for assisting real-time COVID-19 pandemic control – A case study in Hong Kong - Wai-yin Ng; Wai Thoe; Rong Yang; Wai-ping Cheung; Che-kong Chen; King-ho To; Kan-ming Pak; Hon-wan Leung; Wai-kwan Lai; Tsz-kin Wong; Tat-kwong Lau; Ka-wing Au; et al. (Science of The Total Environment, 2023)

Rab7a-mTORC1 signaling-mediated cholesterol trafficking from the lysosome to mitochondria ameliorates hepatic lipotoxicity induced by aflatoxin B1 exposure - Jin-Xian Lin; Chi-Yu Xu; Xin-Mou Wu; Lin Che; Ting-Yu Li; Su-Min Mo; Dong-Bei Guo; Zhong-Ning Lin; Yu-Chun Lin (Chemosphere, 2023)

Aflatoxin B1 exposure triggers hepatic lipotoxicity via p53 and perilipin 2 interaction-mediated mitochondria-lipid droplet contacts: An in vitro and in vivo assessment - Lin Che; Jing Huang; Jin-Xian Lin; Chi-Yu Xu; Xin-Mou Wu; Ze-Bang Du; Jia-Shen Wu; Zhong-Ning Lin; Yu-Chun Lin (Journal of Hazardous Materials, 2023)

Oxygen vacancies endow atomic cobalt-palladium oxide clusters with outstanding oxygen reduction reaction activity - Thomas Yang; Dinesh Bhalothia; Hong-Wei Chang; Che Yan; Amisha Beniwal; You-Xun Chang; Shun-Chi Wu; Po-Chun Chen; Kuan-Wen Wang; Sheng Dai; Tsan-Yao Chen (Chemical Engineering Journal, 2023)

Analyzing landslide-induced debris flow and flow-bridge interaction by using a hybrid model of depth-averaged model and discrete element method - Wen-Jie Shiu; Ching-Fang Lee; Chia-Chi Chiu; Meng-Chia Weng; Che-Ming Yang; Wei-An Chao; Chun-Yuan Liu; Cheng-Han Lin; Wei-Kai Huang (Landslides, 2023)

Two new chromones and a new coumarin from the fruit of Cnidium monnieri (L.) Cusson - Hui-Chi Huang; Chun-Hsiang Lin; Ching-Chuan Kuo; Ming-Der Wu; Ming-Jen Cheng; Jih-Jung Chen; Che-Yi Chao; Guan-Jhong Huang; Yueh-Hsiung Kuo (Natural Product Research, 2023)

Dimerization induces bimodality in protein number distributions - Ming-Yang Ling; Lin-Jie Chiu; Ching-Chu Hsieh; Che-Chi Shu (BioSystems, 2023)

Plasma Matrix Metalloproeteinase-9 Is Associated with Seizure and Angioarchitecture Changes in Brain Arteriovenous Malformations - Yo-Tsen Liu; Cheng-Chia Lee; Chun-Fu Lin; Hsiu-Mei Wu; Wan-Yuo Guo; Huai-Che Yang; Feng-Chi Chang; Kang-Du Liou; Chung-Jung Lin (Molecular Neurobiology, 2022)

Experimental Investigation on Behavior of Single-Helix Anchor in Sand Subjected to Uplift Cyclic Loading - Dongxue Hao; Jianyi Che; Rong Chen; Xin Zhang; Chi Yuan; Xichao Chen (Journal of Marine Science and Engineering, 2022)
Helical anchors have been widely used in geotechnical engineering due to their large uplift resistance. However, the current knowledge of the cyclic performance of helical anchors is still insufficient. Consequently, a series of small-scale model tests are carried out in sand to investigate the influences of embedment ratio, sand compactness and the cyclic parameters on the monotonic, cyclic and post-cyclic performance of single-helix anchors. The tests results indicate that the single-helix anchors with optimal embedment ratio still exhibit a relatively high uplift capacity after suffering cyclic load. The cyclic frequency has the greatest influence on the accumulated displacement, and the influence of amplitude is relatively greater than that of the mean cyclic load. The anchors in dense sand exhibit better performance to resist pullout than those in medium–dense sand under the same cyclic parameter ratios. Moreover, the correlation of post-cyclic uplift capacity and displacement after cyclic loading as well as the possible influence of the upward displacement on the sand flow above the helix are discussed.

The Characteristics and Expression Profile of Peptidoglycan Recognition Protein 2 in the Accessory Nidamental Gland of the Bigfin Reef Squid During Bacterial Colonization - Hau-Wen Li; Wei-Lun Kuo; Chi Chen; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2022)
Some cephalopods carry microorganisms in two specialized organs, the light organ and the accessory nidamental gland (ANG). For the light organ, comprehensive mechanisms have been described for winnowing (bacterial selection) and maintenance of the symbiotic luminescent bacterium Vibrio fischeri ( V. fischeri ). However, the mechanisms controlling bacterial selection and maintenance during bacterial colonization of the ANG are open biological issues with physiological significance. Our recent study on bigfin reef squid ( Sepioteuthis lessoniana ) already showed that the ANG bacterial community shifts gradually and exhibits decreased diversity throughout maturation. This study further describes a potential role of an innate immunity-involved molecule, peptidoglycan recognition proteins (PGRPs), in the ANG of bigfin reef squid during bacterial transmission and colonization. First, we found that four homologs of the PGRP family are expressed in the ANG of bigfin reef squid ( sl PGRP2-5), but only slPgrp2 transcript levels are highly correlated with ANG development and bacterial colonization. Besides, slPgrp2 transcripts are mainly expressed in the epithelial cells of certain secondary tubules of ANG, and the expression levels are varied in the epithelial cells of other secondary tubules. This data reveals that slPgrp2 transcripts may associate with the composition of bacterial consortium and its secretary factors. Moreover, recombinant sl PGRP2 had a negative effect of Escherichia coli ( E.coli ) which inhibited bacterial growth in culture. Therefore, our data suggest slPgrp2 expression in the epithelial cells of secondary tubules in the ANG may have an essential role in the winnowing and maintenance of holobiont homeostasis in bigfin reef squid.

Life span of a landslide dam on mountain valley caught on seismic signals and its possible early warnings - Che-Ming Yang; Jui-Ming Chang; Chi-Yao Hung; Chih-Heng Lu; Wei-An Chao; Keng-Hao Kang (Landslides, 2022)
Outburst flooding after a landslide dam breach causes global fatalities and devastation. Information on the timing, magnitude, and location of the landslide dam is crucial to hazard assessment. Despite recent efforts, successful real-time detection of landslide dams in mountain valleys and dam breakages is rare. Here, we present a series of seismic analysis including landslide detection, identification of landslide dam formations, and monitoring of dam breaches. We show the working of our analysis on a recent landslide dam that occurred in eastern Taiwan. The results indicate that our seismic analysis provides important information on the location and magnitude of landslides and the dam forming based on data acquired from a regional broadband seismic network. Furthermore, we see that the failure of the landslide dam is directly caught by the riverside seismic signals. To provide warning times for impending floods to downstream areas, we believe that proximal high-quality seismic signals along the river channel are viable options for an operational real-time monitoring system, for landslide dams occurring in mountain valleys. Our work can be a starting point to raise awareness in the community.

Towards a rapid assessment of highway slope disasters by using multidisciplinary techniques - Meng-Chia Weng; Cheng-Han Lin; Wen-Jie Shiu; Wei-An Chao; Chia-Chi Chiu; Ching-Fang Lee; Wei-Kai Huang; Che-Ming Yang (Landslides, 2022)
Mega-earthquakes and extreme climate events accompanied by intrinsic fragile geology lead to numerous landslides along mountain highways in Taiwan, causing enormous life and economic losses. In this study, a system for rapid slope disaster information integration and assessment is proposed with the aim of providing information on landslide occurrence, failure mechanisms, and subsequent landslide-affected areas to the highway authority rapidly. The functionality of the proposed system is deployed into three units: (1) geohazard rapid report (GeoPORT I), (2) multidisciplinary geological survey report (GeoPORT II), and (3) site-specific landslide simulation report (GeoPORT III). After landslide occurrence, the seismology-based monitoring network rapidly provides the initial slope disaster information, including preliminary location, event magnitude, earthquake activity, and source dynamics, within an hour. Within 3 days of the landslide, a multidisciplinary geological survey is conducted to collect high-precision topographical, geological, and remote-sensing data to determine the possible failure mechanism. After integrating the aforementioned information, a full-scale three-dimensional landslide simulation based on the discrete element method is performed within 10 days to reveal the failure process and to identify the areas potentially affected by subsequent disasters through scenario modeling. Overall, the proposed system can promptly provide comprehensive and objective information to relevant authorities after the event occurrence for hazard assessment. The proposed system was validated using a landslide event in the Central Cross-Island Highway of Taiwan.

Downregulated Calcium-Binding Protein S100A16 and HSP27 in Placenta-Derived Multipotent Cells Induce Functional Astrocyte Differentiation - Yu-Che Cheng; Chi-Jung Huang; Wei-Chi Ku; Shu-Lin Guo; Lu-Tai Tien; Yih-Jing Lee; Chih-Cheng Chien (Stem Cell Reviews and Reports, 2022)
Little is known about genes that induce stem cells differentiation into astrocytes. We previously described that heat shock protein 27 (HSP27) downregulation is directly related to neural differentiation under chemical induction in placenta-derived multipotent stem cells (PDMCs). Using this neural differentiation cell model, we cross-compared transcriptomic and proteomic data and selected 26 candidate genes with the same expression trends in both omics analyses. Those genes were further compared with a transcriptomic database derived from Alzheimer’s disease (AD). Eighteen out of 26 candidates showed opposite expression trends between our data and the AD database. The mRNA and protein expression levels of those candidates showed downregulation of HSP27, S100 calcium-binding protein A16 (S100A16) and two other genes in our neural differentiation cell model. Silencing these four genes with various combinations showed that co-silencing HSP27 and S100A16 has stronger effects than other combinations for astrocyte differentiation. The induced astrocyte showed typical astrocytic star-shape and developed with ramified, stringy and filamentous processes as well as differentiated endfoot structures. Also, some of them connected with each other and formed continuous network. Immunofluorescence quantification of various neural markers indicated that HSP27 and S100A16 downregulation mainly drive PDMCs differentiation into astrocytes. Immunofluorescence and confocal microscopic images showed the classical star-like shape morphology and co-expression of crucial astrocyte markers in induced astrocytes, while electrophysiology and Ca 2+ influx examination further confirmed their functional characteristics. In conclusion, co-silencing of S100A16 and HSP27 without chemical induction leads to PDMCs differentiation into functional astrocytes. Graphical abstract

Distribution and Catch Rate Characteristics of Narrow-Barred Spanish Mackerel (Scomberomorus commerson) in Relation to Oceanographic Factors in the Waters Around Taiwan - Lu-Chi Chen; Jinn-Shing Weng; Muhamad Naimullah; Po-Yuan Hsiao; Chen-Te Tseng; Kuo-Wei Lan; Che-Chen Chuang (Frontiers in Marine Science, 2021)
This study investigated the relationship of the catch rates (CRs) of Spanish mackerel ( Scomberomorus commerson ) with oceanographic factors in the waters around Taiwan by using high-resolution fishery and environmental data for the period 2011–2016. The investigation results revealed that trammel nets accounted for 69.79% of the total catch of S. commerson and were operated mostly in the Taiwan Strait (TS). We noted seasonal variations in the distribution of high CRs. These CRs were observed in the southwestern TS, including the waters along the southwestern coast of Taiwan and around the Penghu Islands, and extended to the Taiwan Bank during autumn; they increased in winter. To predict the spatial and temporal patterns of Spanish mackerel density and their relationship with oceanographic and spatiotemporal variables, generalized additive models were used. These models explained 48.4% of the total deviance, which was consistent with the assumed Gaussian distribution. Moreover, all variables examined were significant CR predictors ( p < 0.05). Latitude and longitude were the key factors influencing the spatiotemporal distribution of S. commerson , and sea surface chlorophyll a concentration was a key oceanographic factor. Observing projected changes in El Niño/Southern Oscillation events for S. commerson revealed that CRs were higher and distributed further southward during La Niña events than during other events. We inferred that the S. commerson distribution gradually moved toward the southwest with the northeast monsoon, which was enhanced during La Niña in winter.

Intramyocardial injection of human adipose-derived stem cells ameliorates cognitive deficit by regulating oxidative stress–mediated hippocampal damage after myocardial infarction - Tsung-Ming LEE; Cheng-Che LEE; Horng-Jyh HARN; Tzyy-Wen Chiou; Ming-Hsi CHUANG; Chun-Hung CHEN; Chi-Hsuan CHUANG; Po-Cheng LIN; Shinn-Zong LIN (Journal of Molecular Medicine, 2021)
Cognitive impairment is a serious side effect of post-myocardial infarction (MI) course. We have recently demonstrated that human adipose-derived stem cells (hADSCs) ameliorated myocardial injury after MI by attenuating reactive oxygen species (ROS) levels. Here, we studied whether the beneficial effects of intramyocardial hADSC transplantation can extend to the brain and how they may attenuate cognitive dysfunction via modulating ROS after MI. After coronary ligation, male Wistar rats were randomized via an intramyocardial route to receive either vehicle, hADSC transplantation (1 × 10 6 cells), or the combination of hADSCs and 3-Morpholinosydnonimine (SIN-1, a peroxynitrite donor). Whether hADSCs migrated into the hippocampus was assessed by using human-specific primers in qPCR reactions. Passive avoidance test was used to assess cognitive performance. Postinfarction was associated with increased oxidative stress in the myocardium, circulation, and hippocampus. This was coupled with decreased numbers of dendritic spines as well as a significant downregulation of synaptic plasticity consisting of synaptophysin and PSD95. Step-through latency during passive avoidance test was impaired in vehicle-treated rats after MI. Intramyocardial hADSC injection exerted therapeutic benefits in improving cardiac function and cognitive impairment. None of hADSCs was detected in rat’s hippocampus at the 3rd day after intramyocardial injection. The beneficial effects of hADSCs on MI-induced histological and cognitive changes were abolished after adding SIN-1. MI-induced ROS attacked the hippocampus to induce neurodegeneration, resulting in cognitive deficit. The remotely intramyocardial administration of hADSCs has the capacity of improved synaptic neuroplasticity in the hippocampus mediated by ROS, not the cell engraftment, after MI. Key messages Human adipose-derived stem cells (hADSCs) ameliorated injury after myocardial infarction by attenuating reactive oxygen species (ROS) levels. Intramyocardial administration of hADSCs remotely exerted therapeutic benefits in improving cognitive impairment after myocardial infarction. The improved synaptic neuroplasticity in the hippocampus was mediated by hADSC-inhibiting ROS, not by the stem cell engraftment.

Three new species of Cylindrobasidium (Physalacriaceae, Agaricales) from East Asia - Yi-Chung Lin; Chia-Ling Wei; Chi-Yu Chen; Che-Chih Chen; Sheng-Hua Wu (Mycological Progress, 2021)

Syndecan-3 contributes to the regulation of the microenvironment at the node of Ranvier following end-to‑side neurorrhaphy: sodium image analysis - Chiung-Hui Liu; Yu-Chen Kuo; Che-Yu Wang; Chao-Chun Hsu; Ying-Jui Ho; Yun-Chi Chiang; Fu-Der Mai; Wei-Jhih Lin; Wen-Chieh Liao (Histochemistry and Cell Biology, 2021)

Multifunctional Microparticles Incorporating Gold Compound Inhibit Human Lung Cancer Xenograft - Pui -Yan Lee; Chun-Nam Lok; Chi-Ming Che; Weiyuan John Kao (Pharmaceutical Research, 2020)

TNFSF13 upregulation confers chemotherapeutic resistance via triggering autophagy initiation in triple-negative breast cancer - Hui-Yu Lin; Chia-Hao Kuei; Hsun-Hua Lee; Che-Hsuan Lin; Yen-Lin Chen; Chi-Long Chen; Yuan-Feng Lin (Journal of Molecular Medicine, 2020)

First report of leaf blight on Cattleya × hybrid caused by Neoscytalidium dimidiatum in Taiwan - Che-Wei Chang; Chi-Yu Chen; Chih-Li Wang; Wen-Hsin Chung (Journal of Plant Pathology, 2020)

Optimization of air quality monitoring network based on a spatiotemporal-spectrum manifold analysis - Chi-Fang Wang; Ming-Che Hu; Chieh-Han Lee; Hwa-Lung Yu (Stochastic Environmental Research and Risk Assessment, 2019)

Using a numerical method to precisely evaluate the alpha angle in a hip image - Chung-Liang Lai; Wei-Min Chi; Ying-Jui Ho; Chien-Chung Lin; Hsiao-Che Lin; Chin-Liang Kuo; Jian-Horng Chen (Medical & Biological Engineering & Computing, 2019)

A Multifunctional Hydrogel Delivers Gold Compound and Inhibits Human Lung Cancer Xenograft - Puiyan Lee; Chun-Nam Lok; Chi-Ming Che; Weiyuan John Kao (Pharmaceutical Research, 2019)

Energy-Based Brittleness Index and Acoustic Emission Characteristics of Anisotropic Coal Under Triaxial Stress Condition - Jun Zhang; Chi Ai; Yu-wei Li; Ming-guang Che; Rui Gao; Jia Zeng (Rock Mechanics and Rock Engineering, 2018)

Using nonlinear finite element models to analyse stress distribution during subluxation and torque required for dislocation of newly developed total hip structure after prosthetic impingement - Wei-Min Chi; Chien-Chung Lin; Ying-Jui Ho; Hsiao-Che Lin; Jian-Horng Chen (Medical & Biological Engineering & Computing, 2018)

Suppressive effect of microRNA319 expression on rice plant height - Wei-Ting Liu; Peng-Wen Chen; Li-Chi Chen; Chia-Chun Yang; Shu-Yun Chen; GuanFu Huang; Tzu Che Lin; Hsin-Mei Ku; Jeremy J. W. Chen (Theoretical and Applied Genetics, 2017)

Three new species of Hyphodontia s.l. (Basidiomycota) with poroid or raduloid hymenophore - Che-Chih Chen; Sheng-Hua Wu; Chi-Yu Chen (Mycological Progress, 2017)

Theoretical Analysis of Total Hip Dislocation and Comparison of Hemispherical Cup and Newly Developed Cup - Hsiao-Che Lin; Wei-Min Chi; Ying-Jui Ho; Chien-Chung Lin; Jian-Horng Chen (Journal of Medical and Biological Engineering, 2015)

Relationship between road traffic noisescape and urban form in Hong Kong - Kin-Che Lam; Weichun Ma; Pak Kin Chan; Wing Chi Hui; King Lam Chung; Yi-tak Teresa Chung; Chun Yin Wong; Hui Lin (Environmental Monitoring and Assessment, 2013)

Benzodiazepine therapy in psychiatric outpatients is associated with deliberate self-poisoning events at emergency departments—a population-based nested case–control study - Hsin-I Shih; Ming-Chia Lin; Che-Chen Lin; Hsiang-Chin Hsu; Hsin-Ling Lee; Chih-Hsien Chi; Fung-Chang Sung; Yen-Jung Chang; Chia-Hung Kao (Psychopharmacology, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Tail loss compromises immunity in the many-lined skink, Eutropis multifasciata - Chi-Chien Kuo; Chiou-Ju Yao; Te-En Lin; Hsu-Che Liu; Yu-Cheng Hsu; Ming-Kun Hsieh; Wen-San Huang (The Science of Nature, 2013)

Effects of design parameters of total hip components on the impingement angle and determination of the preferred liner skirt shape with an adequate oscillation angle - Hsiao-Che Lin; Wei-Min Chi; Ying-Jui Ho; Jian-Horng Chen (Medical & Biological Engineering & Computing, 2013)

Preliminary evaluation of growth and conformation traits of local goats and Nubians upgraded by a black Boer line in Taiwan - An-Kuo Su; Shen-Suan Yang; Shui-Tsai Chen; Yu-Shin Cheng; Jan-Chi Huang; Ming-Che Wu; Jean-Paul Poivey (Tropical Animal Health and Production, 2012)

Reactive oxygen species-mediated PKC and integrin signaling promotes tumor progression of human hepatoma HepG2 - Chi-Tan Hu; Jia-Ru Wu; Chuan-Chu Cheng; Sindy Wang; Hsiao-Ting Wang; Ming-Che Lee; Ling-Jung Wang; Siou-Mei Pan; Tsu-Yao Chang; Wen-Sheng Wu (Clinical & Experimental Metastasis, 2011)

A critical exploration of blood and environmental chromium concentration among oral cancer patients in an oral cancer prevalent area of Taiwan - Chi-Ting Chiang; Tsun-Kuo Chang; Yaw-Huei Hwang; Che-Chun Su; Kuo-Yang Tsai; Tzu-Hsuen Yuan; Ie-Bin Lian (Environmental Geochemistry and Health, 2011)

A disease associated with phytoplasma in Parthenium hysterophorus - Zhengnan Li; Lei Zhang; Haiyan Che; Hongguang Liu; Ming Chi; Daquan Luo; Yan Li; Wang Chen; Yunfeng Wu (Phytoparasitica, 2011)

A vitronectin M381T polymorphism increases risk of hemangioblastoma in patients with VHL gene defect - Jing-Shan Huang; Chih-Ming Lin; Yu-Che Cheng; Kun-Long Hung; Chih-Cheng Chien; Shao-Kuan Chen; Chih-Ju Chang; Chan-Wei Chen; Chi-Jung Huang (Journal of Molecular Medicine, 2009)

Silver nanoparticles: partial oxidation and antibacterial activities - Chun-Nam Lok; Chi-Ming Ho; Rong Chen; Qing-Yu He; Wing-Yiu Yu; Hongzhe Sun; Paul Kwong-Hang Tam; Jen-Fu Chiu; Chi-Ming Che (JBIC Journal of Biological Inorganic Chemistry, 2007)

Food and feeding habits of ribbonfish Trichiurus lepturus in coastal waters of south-western Taiwan - Wann-Duen CHIOU; Chiee-Young CHEN; Chi-Ming WANG; Che-Tsung CHEN (Fisheries Science, 2006)

Environmental Quality Of Urban Parks And Open Spaces In Hong Kong - Kin-Che Lam; Sai-Leung Ng; Wing-Chi Hui; Pak-Kin Chan (Environmental Monitoring and Assessment, 2005)

Functional genomic analysis of Arabidopsis thaliana glycoside hydrolase family 1 - Zhiwei Xu; Luis Escamilla-Trevio; Lihui Zeng; Mallikarjun Lalgondar; David Bevan; Brenda Winkel; Ali Mohamed; Chi-Lien Cheng; Ming-Che Shih; Jonathan Poulton; Asim Esen (Plant Molecular Biology, 2004)

Bis-intercalative dinuclear platinum(II) 6-phenyl-2,2′-bipyridine complexes exhibit enhanced DNA affinity but similar cytotoxicity compared to the mononuclear unit - Hing-Leung Chan; Dik-Lung Ma; Mengsu Yang; Chi-Ming Che (JBIC Journal of Biological Inorganic Chemistry, 2003)

Comparison between `in vivo' and `in vitro' methods for evaluating tumor angiogenesis using cervical carcinoma as a model - Wen-Fang Cheng; Chien-Nan Lee; Chi-An Chen; Jan-Show Chu; Cheng-Che S. Kung; Chang-Yao Hsieh; Fon-Jou Hsieh (Angiogenesis, 1999)